Action plan proposal to obtain triple certification in a natural gas transportation company - Bueno, Cintia Guerra; Pinheiro, Jorge Lucas Costa; Marques, Wagner da Silveira; Silva, Telma Fidelis Fragoso da; Freitag, Alberto Eduardo Besser (Brazilian Journal of Operations & Production Management, 2024)
Goal: for large gas transportation companies, it is of strategic relevance to be compliant with ISO 9001, ISO 45001, and ISO 14001 certifications, acknowledging their Integrated Management System (IMS). Based on this context, the purpose of this study was to propose an action plan to obtain triple certification for a Brazilian natural gas transportation company. Design / Methodology / Approach: the methodology comprised research of applied nature, exploratory and descriptive objectives, qualitative approach, with a single case study investigation strategy, and data collected through triangulation, combining documents, interviews, and field observation. Results: First, an action plan, which enabled the company to achieve triple certification in ISO 9001, ISO 45001, and ISO 14001 standards. Second, a table correlating seventeen IMS elements with technical and academic literature, and guidance documents of the studied company, making it easier to visualize interdependencies. Limitations of the investigation: The main one is the generalization limit of the conclusions, models or theories developed from a single case study, used in this work. These limitations do not reduce the importance of the results found, since the proposed action plan enabled the natural gas transportation company to obtain the desired triple certification. Practical implications: the proposed action plan may support other companies to achieve triple certification. Originality / Value: no research has been identified in the international literature that deals with triple certification for companies operating in the natural gas transportation market, specifically, the correlation of IMS elements with literature references and guidance documents of the studied company.